El manuscrit II-3096 (Olim 2.Ll.1) de la Biblioteca del Palacio Real - Gimeno Blay, Francisco M. (Caplletra. Revista Internacional de Filologia, 2015)
The author proposes a reconstruction of the structure of this manuscript, made up by the factitious union of two miscellaneous volumes. The manuscript was already described by Massó i Torrents, Round, Blüher, Jorgensen Concheff and Martínez Romero.